Cover Image. (4th April 2018) - Sato, T.; Yamaguchi, M.; Murakami, Y.; Horigome, Y.; Negishi, S.; Kasai, K.
Abstract : The cover image, by Tomonori Sato et al., is based on the Original Article Changes in maxillofacial morphology due to improvement of nasal obstruction in rats, DOI:10.1111/ocr.12220 .